The TKT (Teaching Knowledge Test) Course CLIL Module (Content and Language Integrated Learning) - Bentley K. Kay (Cambridge English)
This course is designed for teachers and trainee teachers preparing for the Cambridge ESOL Teaching Knowledge Test (TKT): Content and Language Integrated Learning (CLIL) module. It is ideal for both content and language teachers. Written by a CLIL expert in collaboration with Cambridge ESOL, this course covers the four key areas of the test: knowledge of CLIL and principles of CLIL, lesson preparation, lesson delivery, and assessment. It will also be useful for anyone seeking an introduction to CLIL theory and practice, as well as teachers working with English as an Additional Language (EAL) learners. The TKT Course CLIL Module introduces teachers to the concepts and terminology central to CLIL and provides an introduction to its main theories, approaches and support strategies. Teachers are then encouraged to apply these to their own teaching contexts and analyse their usefulness for their own learners. CLIL terms and concepts are clearly explained for non-specialist teachers. Model practice test and TKT: CLIL sample tasks help candidates become familiar with the format and style of the TKT exam. Regular concept checking tasks and full answer key make it perfect for self-study. Reflection and discovery activities encourage readers to further explore the topics introduced in the course.